Nuna Nalluyuituq (The Land Remembers): Remembering landscapes and refining methodologies through community‐based remote sensing in the Yukon‐Kuskokwim Delta, Southwest Alaska. Issue 3 (15th July 2021) - Lim, Jonathan S.; Gleason, Sean; Jones, Warren; Church, Willard
Abstract: The following article outlines a collaborative, multidisciplinary approach to remote sensing in Southwest Alaska's Yukon‐Kuskokwim (Y‐K) Delta that combines ethnographic inquiry and remote sensing to monitor, detect and preserve cultural resources for Alaskan Native communities. Because distinctive vegetation differences are readily visible on cultural sites during the summer months, the analysis of multispectral imagery obtained from remote sensing is particularly useful. In turn, we demonstrate the efficacy of this protocol on pre‐contact settlement sites along the Ayakulik River system on Kodiak Island using a normalized difference vegetation index (NDVI) raster of the study area. Here, support vector machine (SVM) supervised classification was highly effective at identifying spectral patterns associated with anthropogenic activity while ethnographic data helped rule out false‐positive cases. In addition, we provide the results of a 2019 archaeological prospection survey carried out in conjunction with the ongoing Nunalleq Project in Quinhagak, Alaska, to further highlight the value of ethnographic data collection, ethnobotanical surveys and unmanned aerial vehicle (UAV)‐based spectroscopy alongside SVM supervised classification. Finally, we propose three suggestions for future research on Yup'ik landscapes in the Y‐K Delta regarding citizen science, language preservation and the use of collaborative online maps for community‐based decision making.